การวิเคราะห์อภิมานปัจจัยเชิงเหตุของคุณภาพชีวิตการทำงานของพยาบาล - ศิริญญา คงอยู่ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purposes of this meta-analysis study were to 1) describe research characteristics of antecedent variables of nurses’ quality of working life 2) identify the factor that influence antecedent variables of nurses’ quality of working life 3) compare mean of correlation coefficients across antecedent variables and research characteristics and 4) analyze predictors of correlation coefficients by research characteristics variables. The 44 Thai researches studied during 1987-2014 were recruited. Study moderators including general, substantive, methodological characteristics and research quality were collected. There were 213 correlation coefficients analyzed by using meta-analysis method of Glass, et al. Statistics used in this study were t-test, ANOVA and Hierarchical stepwise regression analysis. The major finding were as follows: 1) The research characteristics consisted of 3 components including general, substantive and methodological characteristics. 2) The antecedent variables were 5 factors including management factor (r=.57), organizational factor (r=.55), working factor (r=.38), personal trait factor (r=.36) and personal background factor (r=.07) respectively. 3) Publication year, research quality, reliabilities of research instrument and sample size were statistically and significantly affected on the mean of correlation coefficients of antecedent variables of nurses’ quality of working life, at .05 level. And 4) The predictors of correlation coefficients of antecedent variables were management, organizational climate, job description, participation, organizational commitment, organizational culture, attitude toward nursing profession, relationship, job satisfaction, motivation, work values, professional competency, leadership of head nurses, organizational support, job enrichment, job stress, burn out and sample size predicted research. They were accounted for 64.6 % of variance.